Oligonucleotide abundance biases aid design of a type IIS synthetic genomics framework with plant virome capacity. Issue 5 (11th February 2021) - Pasin, Fabio
Abstract: Synthetic genomics‐driven dematerialization of genetic resources facilitates flexible hypothesis testing and rapid product development. Biological sequences have compositional biases, which, I reasoned, could be exploited for engineering of enhanced synthetic genomics systems. In proof‐of‐concept assays reported herein, the abundance of random oligonucleotides in viral genomic components was analyzed and used for the rational design of a synthetic genomics framework with plant virome capacity (SynViP). Type IIS endonucleases with low abundance in the plant virome, as well as Golden Gate and No See'm principles were combined with DNA chemical synthesis for seamless viral clone assembly by one‐step digestion‐ligation. The framework described does not require subcloning steps, is insensitive to insert terminal sequences, and was used with linear and circular DNA molecules. Based on a digital template, DNA fragments were chemically synthesized and assembled by one‐step cloning to yield a scar‐free infectious clone of a plant virus suitable for Agrobacterium ‐mediated delivery. SynViP allowed rescue of a genuine virus without biological material, and has the potential to greatly accelerate biological characterization and engineering of plant viruses as well as derived biotechnological tools. Finally, computational identification of compositional biases in biological sequences might become a common standard to aid scalable biosystems design and engineering. Abstract : Novel methodological concepts for biosystems engineering are necessary to meet the ever‐increasing human needs. In this study, compositional biases of biological sequences have been identified and exploited to design SynViP—a synthetic genomics framework with plant virome capacity. SynViP allowed rescue a genuine virus based on a digital template and it has the potential to greatly accelerate the biological characterization and engineering of plant viruses and derived biotechnologies.